Numerical simulation and dynamical system for solving biomathematical model with optimal control - A.M.S. Mahdy; D.S. Mohamed (Franklin Open)
This study shows that have understand SEIASqEqHR models work dynamically and we have depended on the Legendre-Galerkin procedure to explain that. We have displayed the creation of a brand new flow chart that displays the coronavirus form. The SEIASqEqHR form is based on the Legendre-Galerkin method. The proposed number-based ways of doing things are fantastic. Our statistical analysis has revealed that social isolation between potentially infected carriers of the illness and healthy people may be able to stop or slow the illness from spreading. The outcomes are expressed mathematically and emotionally detached from the projections. The coronavirus model's free balance and dependability emphasis are computed. Additionally, it is shown that a consistent, regular pattern exists. The outcomes are very good; we are getting them using the Matlab program. This model with order derivatives defined in this style had not previously been calculated. The changing system for this model is discussed. This model's best control and the number-based way of doing things for the test run that appears to have a control problem are also discussed.